Solid food in typhoid fever - Nafsiah Mboi; Sri Rochani Sudjarwo; Corry Matondang; Suharjono Suharjono; Sutedjo Sutedjo (Paediatrica Indonesiana, 1973)
Typhoid fever (enteric Fever, typhus abdominalis) is still a commoninfectious disease in Indonesia, the chief manifestations of which arein the intestines. It is however not an intestinal disease. The early involvement of Peyer's patches with their subsequent coagulative necrosis and resulting ulcerations is the outstanding pathologic feature. In addition, there are extensive changes in the liver, with involvement of the gall-bladder and bile passages. All this interferes with digestion, but strange to say, to a much less extent than the pathologic anatomy would lead one to expect. In spite of all these changes, food is digested and absorbed remarkably well (Mc. Lester, 1952).